Central pontine myelinolysis as a complication of hyperemesis gravidarum - Mayner-Tresol, Gabriel (2018)
Central pontine myelinolysis or osmotic demyelination syndrome is a disorder consisting of non-inflammatory demyelination, involving the pons, secondary to swallowing or neuronal edema in patients with severe hyponatremia undergoing rapid sodium replacement, which is considered the main pathophysiological mechanism. The clinical manifestations are diverse and some cases have been reported in pregnant women with hyponatremia induced by severe hyperemesis gravidarum. There is no evidence regarding optimal treatment or prognosis, so it is essential to recognize hyponatremia and perform an adequate correction of sodium levels to avoid this complication. We present the case of a 21-year-old woman with a 12-week pregnancy who presented gait distrubances, polydipsia, speech disorders, dysphonia and intense vomiting with alterations in serum sodium levels. Cerebral magnetic resonance imaging revealed symmetrical hypointense lesions in the region of the pons, with no mass effect or compression of adjacent structures suggestive of osmotic demyelination.